AKUNTABILITAS GEREJA DALAM PERSPEKTIF ALKITABIAHDAN STEWARDSHIP THEORY (Study Kasus pada Gereja X di Jawa Timur) - Franchisca Sukmawati; Sri Pujiningsih; Nujmatul Laily (Jurnal Akuntansi Aktual, 2016)
Abstract:This research has purpose to understand of practice financial accountability at X church inEast Java. This research use qualitative approach. Procedure and collecting data in this research byusing technique interview, documentation, and hidden observation. Interview conducted for regent,herdsman session, management and congregation. Result of this research show : 1) Vertical financialaccountability or for God conducted by manage cash church honestly and full of responsbility. 2)Horizontal financial accoountability form by publish financial report.Keywords:Horizontal Accountability, Vertical Accountability, Stewardship Theory, Church